Water resistance of ceramzite containing galvanoteciinical slime/Keramzito, turinčio galvanotechninio šlamo, atsparumas vandeniui - Kazragis, Algimantas; Zalieckienė, Elena; Kulinič, Halina; Milčiūnienė, Violeta (Journal of Civil Engineering and Management, 1997)
In the Lithuanian metal working plants galvanotechnical slime is formed during the manufacturing process. It consists of Fe, Ca, Mg and combinations of microelements Cr, Mn, Co, Ni, Cu, Zn, Cd, Pb such as hydroxide, sulphide etc. To prevent contamination of the environment by metal combinations contained in the galvanotechnical slime it has to be utilized for ceramic products during the manufacturing process. In Lithuania the galvanotechnical slime is utilized for ceramzite produced in the Palemonas factory. The aim of this work is to find out whether the microelements contained in galvanotechnical slime are emitted from ceramzite into the environment while ceramzite is affected by water. There is hydromical clay in Lithuania. Cremate clay contains 70–95% of hydromicas, 5–30% kaolinite, and up to 5% of chlorite and traces of montmorillonite. It contains quartz, feldspars, calcite and limonite as well. Oxidical structure (%) is: SiO2 48–51, Al2O3 + TiO2 14–19, Fe2O3 5–8, CaO 7–11, MgO ∼ 3, K2O ∼ 3, Na2O ∼ 1, SO3 up to 0.4, loss by roasting 10–13. In producing ceramzite (1050–125°C) mullite, quartz, hematite, magnetite, anorthite, spinel, forsterite etc. are formed from clay components. If ceramzite contains galvanotechnical slime, the microelements along with ceramzite components compounds thermodynamically a few of Ca, Mg, Fe, Ni, Cu, Zn silicates and aluminates and Ca, Mg, Ni, Cu ferrites. The amount of microelements transferring from ceramzite into water has been defined with the atomicabsorption spectroscopy by keeping ceramzite granules in distilled water for 3,6 and 12 months. The results of the investigation demonstrate that the compounds of Cr, Ni, Cd, Pb, Mn, and Co do not transfer from ceramzite into water. The amounts of metallic compounds in the water C H 2 O are limited by the values of their solubility product L: C H2O = 5,62 Cmax L0,087, The amount of metallic compounds in the water CH2Odepends on the extraction length according to the satiation curve. The results of the investigation show that ceramzite containing galvanotechnical slime is an ecologically clean heat insulating substance. Article in Lithuanian. First Published Online: 26 Jul 2012